2013
DOI: 10.1161/circulationaha.113.002238
|View full text |Cite
|
Sign up to set email alerts
|

Intramyocardial Adiposity After Myocardial Infarction

Abstract: Intramyocardial adiposity, in association with myocardial discontinuity within left ventricular scar borders, is a significant factor associated with altered electrophysiological properties, aberrant connexin43 expression, and increased propensity for VT after MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(35 citation statements)
references
References 50 publications
1
33
0
1
Order By: Relevance
“…The abundantly present ECM is interlaced with phenotypically diverse groups of cells: interstitial fibroblast-like cells (both functionally and structurally heterogeneous, endothelial cells, vascular smooth muscle, surviving cardiomyocytes, immune cells, neurons, and adipocytes [18, 19] (Fig. 1B,C).…”
Section: The Scar – a Living Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…The abundantly present ECM is interlaced with phenotypically diverse groups of cells: interstitial fibroblast-like cells (both functionally and structurally heterogeneous, endothelial cells, vascular smooth muscle, surviving cardiomyocytes, immune cells, neurons, and adipocytes [18, 19] (Fig. 1B,C).…”
Section: The Scar – a Living Tissuementioning
confidence: 99%
“…immune cells) are more than likely. Interactions of fibroblasts with adipocytes within the scar has been suggested to affect conduction velocity via electrotonic source-sink alterations in human MI studies [19], although no mechanism of electrotonic coupling between these cell types has been identified so far [18]. …”
Section: The Many Roles Of Scar Fibroblastsmentioning
confidence: 99%
“…On heart injuries, such as myocardial infarction, millions of cardiomyocytes undergo irreversible necrosis and infarct areas are replaced with fibroblasts and further differentiate into nonfunctional tissues like fibrotic scar [2] or adipose tissue [3, 4]. Recently, targeting fibroblasts by introduction of three transcription factors Gata4, Mef2C and Tbx5 (G, M and T), and reprogramming them into cardiomyocyte-like cells have shown therapeutic potential [5–8].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Pouliopoulos et al have demonstrated that increased intramyocardial adipose tissue in sheep is significantly associated with altered electrophysiological properties such as slower conduction velocity and lower electrogram amplitude, and has an impact on scar-related VT circuits. 10 Computed tomography (CT) offers higher spatial resolution and can identify fat tissue based on CT attenuation density values (Hounsfield units, HU). 36 In addition, contrast-enhanced computed tomography (CE-CT) can accurately define anatomical structures including chamber boundaries and coronary arteries, which can be integrated into electroanatomic mapping (EAM) systems.…”
Section: Introductionmentioning
confidence: 99%